Suicides in Perú: Epidemiological description through SINADEF in the period 2017-2021. - Contreras-Cordova, Coco R. (2022)
Objectives: Description of epidemiological features of suicides in Peru between the years 2017-2021. Material and Methods: Descriptive-comparative study based on the review of the national computerized registry of SINADEF deaths between the years 2017-2021; the final sample included a total of 2579 suicides. Results: Male gender reached 69.5%, average age 34.87 years, 79.5% were single, and 26.6% had complete secondary education. The departments with highest frequency of suicides were Lima (20.3%), Arequipa (19.2%), Cusco (9.5%) and Junín (7.8%). According to ICD-10, the main cause of death was cerebral edema (22.71%), and place of death at home (63.4%). Suicide modalities included hanging (56.6%), poisoning (29.2%), firearm (4%), precipitation (3.1%), and knife (1.7%). It was possible to establish significant differences with a p<0.05 value in: type of suicide and gender, 74% of hangings among males; type of suicide and natural region: hanging in the coast (60%); type of suicide and age range: hanging 10-19 years (27.7%) and poisoning 20-29 years (26.5%). A majority (70.7%) died at home by hanging, followed by poisoning in health facilities (56.9%), and by precipitation (16.8%) on public roads. Conclusions: The most frequent type of suicide was by hanging in young-adult males, and poisoning among females.